Evaluasi Program Wirausaha Pemula Di Kementrian Koperasi dan Ukm Ri : Individualized Outcome Evaluation Terhadap Lima Peserta Program Wirausaha Pemula Di Dki Jakarta Tahun 2012 - Ansar, Andi Besse; Rahayu, Ety (UI Scholars Hub, 2014)
The study discusses about individualized outcome evaluation of young entrepreneur program evaluation at ministry of cooperatives and small medium enterprises for five beneficiaries from Jakarta City in 2012. This research used a qualitative approach with evaluation research. While collecting data using in-depth interview with 7 informans which consist 5 beneficiaries program and 2 program staff. This result of study show that 4 beneficiaries has achieve an outcome program because of the trainee characteristics, training design, work environment, attitude and self concept and design entrepreneurship factors support and 1 beneficiaries has a barrier in work environment, attitude and self concept and entrepreneurship design factors.